El impacto de la inteligencia artificial en el Derecho - Morales Cáceres, Alejandro (2021)
The author examines the relationship between artificial intelligence —as well as the different technologies derived from it— and Law as we know it today. He explores the most recent legal dilemmas related to growing and increasingly advanced technology. The imminent challenge to various basic concepts and principles of law, as well as the future of lawyers’ role are urgent questions, which the author includes in this article.